Common social determinants for overweight and obesity, and dental caries among adolescents in Northern Norway: a cross-sectional study from the Tromsø Study Fit Futures cohort - Stangvaltaite-Mouhat, Lina; Furberg, Anne-Sofie; Drachev, Sergei Nikolaevich; Trovik, Tordis A (BMC Oral Health, 2021)
Background - Non-communicable general and oral health conditions share common risk factors. Studies investigating common social determinants as risk factors for overweight/obesity and dental caries among the same adolescents are scarce and inconclusive. Methods - This cross-sectional study included data from 464 girls and 494 boys from the population-based Tromsø study Fit Futures, which included first-year students attending upper secondary school in 2010–2011 from two municipalities in Northern Norway (1038 participants in total, 93% participation rate). Multivariable binary logistic regression analyses stratified by sex were used to investigate the association between socioeconomic position indicators (adolescent’s own study program, parents’ education and employment status) and overweight/obesity indicated by body weight and waist circumference, untreated dental caries in dentine, and when these conditions were considered simultaneously. Results - Boys enrolled in the general studies and sports programs (versus vocational) had lower odds of being overweight/obese (POR 0.42, 95% CI 0.20–0.86 and POR 0.24, 95% CI 0.08–0.73, respectively), of having high waist circumference (POR 0.39, 95% CI 0.21–0.75 and POR 0.25, 95% CI 0.10–0.64, respectively), dental caries (POR 0.57, 95% CI 0.32–0.99 and POR 0.47, 95% CI 0.22–0.98, respectively), and being simultaneously overweight/obese, having high waist circumference and dental caries (POR 0.24, 95% CI 0.07–0.81 and POR 0.11, 95% CI 0.01–0.98, respectively). Girls enrolled in the general studies program (versus vocational) had lower odds of having dental caries (POR 0.50, 95% CI 0.30–0.84). Conclusions - Adolescent’s own study program was identified to be a common social determinant for overweight/obesity and dental caries among boys. These results support the broader concept of social determinants as common risk factors for general and oral health conditions, and call for common health promotion strategies addressing these common social determinants among adolescents. ...